Conformation Based in silico Studies of Cyclic Tetrapeptides with βγ Fused Turns as Thrombin Inhibitors. Issue 11 (14th March 2023) - Ghosh, Uttam; Kumar, Vikash; Singh, Gajendra; Kanti Chakraborty, Tushar
Abstract: The enormous social and economic consequences of thrombotic diseases, as well as the significant dangers associated with present medications, need the development of more effective and safer anticoagulants. In silico structure‐based design was used to find new peptide‐based thrombin inhibitors and cyclic peptide‐based molecules are attracting wide attention in that regard. Here we have shown the synthesis, conformational and in silico analysis of tetrahydrofuran amino acid (TAA) based 15‐membered cyclic tetrapeptides (CTPs) containing guanidine side chain as thrombin inhibitors. Solution NMR conformational analysis suggests that the βγ fused structures of CTPs are retained in the core and there is no effect of guanidine functionality on the scaffold. Molecular docking results showed that these CTPs can inhibit thrombin protein by interacting with Asp189 residue and the core structure helps to retain the guanidine group inside the active site of protein without any alteration in the backbone H‐bonding. Overall, we have presented here the synthesis, conformational analysis of TAA containing cyclic tetrapeptides along with their docking study against thrombin protein. Further these results will help to design peptide based novel thrombin inhibitors. Abstract : Conformational and in silico analysis of tetrahydrofuran amino acid based cyclic tetrapeptides (CTPs) with guanidine side chain showed that these CTPs can inhibit thrombin by interacting with its Asp189 residue. The core structure with βγ fused turns guides the guanidine group inside the active site of the protein.